2014
DOI: 10.1016/j.celrep.2013.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Pain without Nociceptors? Nav1.7-Independent Pain Mechanisms

Abstract: SummaryNav1.7, a peripheral neuron voltage-gated sodium channel, is essential for pain and olfaction in mice and humans. We examined the role of Nav1.7 as well as Nav1.3, Nav1.8, and Nav1.9 in different mouse models of chronic pain. Constriction-injury-dependent neuropathic pain is abolished when Nav1.7 is deleted in sensory neurons, unlike nerve-transection-related pain, which requires the deletion of Nav1.7 in sensory and sympathetic neurons for pain relief. Sympathetic sprouting that develops in parallel wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 64 publications
7
157
1
1
Order By: Relevance
“…16 Following intraplantar injection of CFA in the left hind paw, inflammation develops in the affected (ipsilateral) hind paw. On day 2 after CFA administration, mice received an ip dose of either test compound 3 (as Na-salt 3a) or the vehicle.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…16 Following intraplantar injection of CFA in the left hind paw, inflammation develops in the affected (ipsilateral) hind paw. On day 2 after CFA administration, mice received an ip dose of either test compound 3 (as Na-salt 3a) or the vehicle.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…These receptors, such as the P2X3 receptor 37,38 and TRPV1 receptor, 39 have an effect on the overall pain behaviour; however, a recent study has demonstrated that we might have to think beyond the traditional classification of nociceptive neurons and sensory processing to effectively target cancer-induced bone pain. 40 Traditionally, the nociceptors have been classified based on expression of specific ion channels and receptors, such as the Nav1.7 and Nav1.8, and it is generally accepted that more than 90% of the nociceptors express Nav1.8. However, in the study by Minett et al, 40 it was demonstrated that the normal function of the Nav1.7-and Nav1.8-positive neurons was not critical for the development of pain behaviour in a mouse model of cancerinduced bone pain despite the fact that these Navs are highly essential for many other pain phenotypes.…”
Section: Peripheral Pain Mechanismsmentioning
confidence: 99%
“…At the same time, oxaliplatin-induced neuropathic pain, a condition that exhibits mechanical and cold allodynia, was not alleviated by Na V 1.7 knockout even when Na V 1.7 was also removed from sympathetic neurons 186 . Cancer-induced bone pain and resultant gait abnormalities were also not significantly affected by Na V 1.7 knockout in all peripheral neurons 186 . There are also pain conditions that are only partially alleviated by Na V 1.7 knockout in Na V 1.8-positive neurons, such as allodynia following a burn injury 187 .…”
Section: Na V 17mentioning
confidence: 81%
“…While global Na V 1.7 knockout in mice was shown to be non-responsive to a range of neuropathic pain conditions and demonstrated deficiencies in acute pain sensing 175 , it is now evident that Na V 1.7 is not responsible for all that is painful 2,178,186 , dashing the hopes that the Na V 1.7 channel may be a panacea for all pain. The subsequent surging interest in the role of Na V channels in pain have revealed that other Na V isoforms, in particular Na V 1.6 and Na V 1.8, also play a major part in noxious sensing 2,186,197,198,205,207,349,350 , suggesting that further understanding of Na V 1.6 and Na V 1.8 may help us to decipher the pathophysiological mechanisms of pain.…”
Section: Chapter 6 -Overall Conclusionmentioning
confidence: 99%
See 1 more Smart Citation